Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How to find the sum of the following series

$$\frac{1}{5} - \frac{1\cdot 4}{5\cdot 10} + \frac{1\cdot 4\cdot 7}{5\cdot 10\cdot 15} - \dots\,.?$$

I have no idea. I have written the general term and tested its convergence by Gauss' test for convergence, but they are neither the question nor the answer.

share|improve this question
    
Could you reveal what your general term is? It is not clear what the pattern in "1, 4, 7, ..." is supposed to be. –  Henning Makholm Jan 12 at 2:39
1  
The general term is $$\frac{(-1)^{n-1}}{5^n}. \frac{1.4.7. \dots (3n-2)}{n!}$$. $1, 4, 7,\dots$ is in an AP. What to do after it? –  Dutta Jan 12 at 2:45
    
See binomial series. –  Lucian Jan 12 at 3:02

3 Answers 3

up vote 4 down vote accepted

From the Generalized Binomial Theorem (for $|x|<1$), $$\left(1+x\right)^n=1+nx+\frac{n(n-1)}{2!}x^2+\frac{n(n-1)(n-2)}{3!}x^3+\cdots$$

Method $1:$

$\displaystyle -\frac{1\cdot 4\cdot 7}{5\cdot 10\cdot 15}=\frac{-\frac13\left(-\frac13-1\right)\left(-\frac13-2\right)3^3}{3!\cdot 5^3}=\frac{-\frac13\left(-\frac13-1\right)\left(-\frac13-2\right)}{3!}\left(\frac35\right)^3 $

and $\displaystyle \frac{1\cdot 4}{5\cdot 10}=\frac{-\frac13\left(-\frac13-1\right)3^2}{2!\cdot 5^2}=\frac{-\frac13\left(-\frac13-1\right)}{2!}\left(\frac35\right)^2$

and $\displaystyle-\frac15=\left(-\frac13\right)\left(\frac35\right)$

So, the given series $\displaystyle=1-\left(1+\frac35\right)^{-\frac13}$


Method $2:$

If $\displaystyle nx=-\frac15 \ \ \ \ (1)$

and $\displaystyle\frac{n(n-1)}{2!}x^2=-\frac{1\cdot4}{5\cdot10}=\frac2{25} \ \ \ \ (2)$

Divide $(2)$ with the square of $(1)$ to get $n$ and then $x$ using $(1)$

and check that $x,n$ satisfies $\displaystyle\frac{n(n-1)(n-2)}{3!}x^3=-\frac{1\cdot 4\cdot 7}{5\cdot 10\cdot 15}$

share|improve this answer
    
@HopelessFool, how about this method? –  lab bhattacharjee Jan 12 at 5:39
    
Higher Secondary mathematics. Half forgotten. My fault no doubt. I do not understand why these are asked in NBHM! Thank you. –  Dutta Jan 12 at 6:08

For any $\gamma \in \mathbb{R}$ and $k \in \mathbb{N}$, let $(\gamma)_k = \gamma(\gamma+1)\cdots(\gamma+k-1)$ be the rising Pochhammer symbol. Using following expansion $$\frac{1}{(1-z)^\gamma} = \sum_{k=0}^\infty \frac{(\gamma)_k}{k!} z^k$$ We can evaluate the sum as

$$\sum_{k=1}^\infty (-1)^{k-1}\frac{\prod_{j=0}^{k-1}(3j+1)}{5^kk!} = - \sum_{k=1}^\infty \frac{(\frac13)_k}{k!}\left(-\frac{3}{5}\right)^k = 1 - \frac{1}{\sqrt[3]{1+\frac{3}{5}}} = 1 - \frac{\sqrt[3]{5}}{2} $$

share|improve this answer

According to Maple, $$ \sum_{m=0}^\infty (-1)^m \dfrac{\prod_{j=0}^m (1+3 j)}{\prod_{j=0}^m (5 + 5 j)} = 1 - \dfrac{5^{1/3}}{2}$$

share|improve this answer
    
Dear Sir, I do not know Maple. The left hand side is the general term written differently. How to get the the left hand side by manual computation? –  Dutta Jan 12 at 2:56

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.